Pancreas development is promoted by cyclopamine, a Hedgehog signaling inhibitor - Kim, Seung K. (The National Academy of Sciences, 1998)
Exposure to cyclopamine, a steroid alkaloid that blocks Sonic hedgehog (Shh) signaling, promotes pancreatic expansion in embryonic chicks. Heterotopic development of pancreatic endocrine and exocrine structures occurs in regions adjacent to the pancreas including stomach and duodenum, and insulin-producing islets in the pancreas are enlarged. The homeodomain transcription factor PDX1, required for pancreas development, is expressed broadly in the posterior foregut but pancreas development normally initiates only in a restricted region of PDX1-expressing posterior foregut where endodermal Shh expression is repressed. The results suggests that cyclopamine expands the endodermal region where Shh signaling does not occur, resulting in pancreatic differentiation in a larger region of PDX1-expressing foregut endoderm. Cyclopamine reveals the capacity of a broad region of the posterior embryonic foregut to form pancreatic cells and provides a means for expanding embryonic pancreas development.